Increasing the fire retardant properties of oriented chip board - Gazizov Asgat; Permyakov Arseniy; Gaynutdinov Ruslan (E3S Web of Conferences)
This article explores the impact of various factors on the increase in the fire-retardant properties of OSPs, the justification of the temperature regime of OSP impregnation, and the impregnation time. Using a specialized installation for testing building materials for flammability (HSR installation), the study achieves determine the effectiveness of the impregnation composition for samples at various temperatures and impregnation times. Experimental research confirms the effectiveness of the impregnation composition for samples depending on various temperatures and impregnation times, offering new possibilities for safer structures and materials. Continued research may yield even better wood protection methods, reducing fire risk and preserving lives and property.